Determinan Terjadinya Infeksi Luka Operasi (ILO) Post Sectio Caesarea - Rina Kartikasari; Nelly Apriningrum (Faletehan Health Journal, 2020)
One of efforts in saving the lives of mothers and babies as the main goal of the delivery process can be through obstetric surgical procedures of caesarean section. The surgical procedures of cesarean section delivery can cause several complications, one of which is surgical site infection (SSI). The purpose of this study was to determine the factors associated with the incidence of surgical site infection (SSI) of post caesarean postpartum mothers at Berkah General Hospital Pandeglang in 2017. This study used an analytical survey research method with a cross-sectional approach. This research was conducted from May to June 2017 at the postpartum room. The research samples were 96 respondents. The sampling technique is accidental sampling. The data collection technique used a questionnaire and direct observations. The data analysis used chi square test. The results showed that out of 96 post cesarean postpartum, 77.1% did not experience SSI. There was a relationship among nutritional status (Pv 0.000; OR 1.8), hemoglobin level (Pv 0.003; OR 8.9), wound care (Pv 0.000) and the incidence of SSI. However, there was no relationship between maternal age (Pv 0.327) and parity (Pv 0.889) and the incidence of SSI. The risk factors of post caesarean section surgical site infection are nutritional status, hemoglobin level, and wound care.